Asymptotically-Flat Black Hole Solutions in Symmergent Gravity - Pulice, Beyhan; Pantig, Reggie C.; Övgün, Ali; Demir, Durmus (Wiley-V C H Verlag Gmbh, 2024)
Symmergent gravity is an emergent gravity model with an R+R2$R+R<^>2$ curvature sector and an extended particle sector having new particles beyond the known ones. With constant scalar curvature, asymptotically flat black hole solutions are known to have no sensitivity to the quadratic curvature term (coefficient of R2$R<^>2$). With variable scalar curvature, however, asymptotically-flat symmergent black hole solutions turn out to explicitly depend on the quadratic curvature term. In the present work, asymptotically-flat symmergent black holes with variable scalar curvature are constructed and used its evaporation, shadow, and deflection angle to constrain the symmergent gravity parameters. Concerning their evaporation, new particles predicted by symmergent gravity are found, even if they do not interact with the known particles, can enhance the black hole evaporation rate. Concerning their shadow, statistically significant symmergent effects are reached at the 2 sigma$2\,\sigma$ level for the observational data of the Event Horizon Telescope (EHT) on the Sagittarius A* supermassive black hole are shown. Concerning their weak deflection angle, discernible features for the boson-fermion number differences are revealed, particularly at large impact parameters. These findings hold the potential to serve as theoretical predictions for future observations and investigations on black hole properties.
Keywords: black hole deflection angle; black hole shadow; black holes; hawking radiation; symmergent gravity